Poor performance and the value of corporate honesty - Chance, Don; Cicon, James; Ferris, Stephen P. (Journal of Corporate Finance, 2015)
We examine a sample of companies that make announcements attributing blame for recent poor performance to either themselves or an external factor. We find that both groups of companies exhibit poor company-specific performance prior to the announcement, indicating that companies blaming external factors are not being truthful. Following the announcement, companies that blame themselves begin to perform better while those that blame others continue their weak performance. We find no differences in the financial and governance characteristics of these companies. Companies that blame themselves, however, provide more detailed information about the source of the problem, while those that blame others offer only vague generalizations. Our results suggest that managerial honesty and forthrightness have value to shareholders since they imply that the company is more likely to make the corrections necessary to achieve stronger future performance.